Artificial Intelligence and employee's health - new challenges - Jolanta Walusiak-Skorupa; Paulina Kaczmarek; Marta Wiszniewska (Nofer Institute of Occupational Medicine, 2023)
Background The presence of artificial intelligence (AI) in many areas of social life is becoming widespread. The advantages of AI are being observed in medicine, commerce, automobiles, customer service, agriculture and production in factory settings, among others. Workers first encountered robots in the work environment in the 1960s. Since then, intelligent systems have become much more advanced. The expansion of AI functionality in the work environment exacerbates human health risks. These can be physical (lack of adequate machine control, accidents) or psychological (technostress, fear, automation leading to job exclusion, changes in the labour market, widening social differences). Material and Methods The purpose of this article is to identify, based on selected literature, possible applications of AI and the potential benefits and risks for humans. Results The main area of interest was the contemporary work environment and the health consequences associated with access to smart technologies. A key research area for us was the relationship between AI and increased worker control. Conclusions In the article, the authors emphasize the importance of relevant EU legislation that guarantees respect for the rights of the employed. The authors put forward the thesis that the new reality with the widespread use of AI, requires an analysis of its impact on the human psycho-social and health situation. Thus, a legal framework defining the scope of monitoring and collection of sensitive data is necessary. Med Pr. 2023;74(3):227-33